IMPLEMENTASI PENGUJIAN MODEL TAM PADA APLIKASI QRIS MERCHANT: STUDI EMPIRIS DI KOTA BENGKULU - Ardhana, Amelia; Usman, Berto (FEB Universitas Sam Ratulangi Manado, 2024)
The increased adoption of QRIS by merchants, serving as an innovative and efficient payment alternative, holds the potential to support the GNNT and facilitate the transition towards a cashless society. While the provision of QRIS by merchants yields numerous benefits, not all users readily embrace its utilization. This research aims to gauge the acceptance of QRIS implementation by merchants, employing the TAM for testing. The study population consists of traders utilizing QRIS in Bengkulu City. Utilizing SEM analysis with Smart PLS 4 on a sample size of 128 participants, this research scrutinizes merchant acceptance of QRIS by examining perceived usefulness, perceived ease of use, attitudes towards using, and actual use. Empirical findings reveal that perceived usefulness and perceived ease of use exert a partially positive and significant impact on attitudes toward using. Additionally, perceived usefulness exhibit a positive and significant effect on actual use. Conversely, perceived ease of use demonstrates a positive but nonsignificant effect on actual use. The research also underscores that attitudes towards usage positively and significantly influence actual usage. Ultimately, the acceptance of QRIS by merchants is shaped by the perceived usefulness and ease of use, with attitudes playing a pivotal role in determining overall aceptance.